From the north : a simple and modern approach to authentic Nordic cooking - Björk, Katrín (Page Street Publishing Co., 2018)
'Katrín Björk celebrates the flavors of her childhood with fresh ingredients and unique twists. Her modern techniques make traditional Nordic cooking simple and approachable, no matter how far south your kitchen. With helpful tips on how to select the freshest fish, preserve ingredients safely and bake the rustic bread essential to any Nordic meal, its easy to make these dishes your own. Though Katrín isnt afraid to break a few rules in the name of convenience and flavor, her recipes remain rooted in the connection to nature and family that is at the heart of Nordic life.' --amazon.com.